Coronary Aneurysm Occurring Late after Drug-Eluting Stent Implantation. (11th May 2011) - Abergel, Etan; Roguin, Ariel
Abstract : Drug-eluting stents may affect the normal healing process of the vessel wall and the remodeling process and may lead to late stent malapposition (LSM). The known incidence of this phenomen originates from short-term angiographic follow-up studies. We describe a case report of very late stent malapposition and marked positive vessel remodeling 3 years after sirolimus-eluting coronary stent implantation. Angiography performed one year after stent implantation was normal. Thus, the abnormalities developed sometime between years 1 and 3. The cause is unknown, but it is reasonable to suggest a local effect of the medication/polymer of the stent. LSM rate and aneurysmal formation is higher in DES than in BMS and may be associated with increased risk for late stent thrombosis. Currently, the risk of very late stent thrombosis after DES implantation is of major concern. As observed in this case report, LSM might occur and develop very late. This has significant consequences especially to the many asymptomatic patients with DES implanted many years ago and the recommendation of dual antiplatelet therapy. More studies with late and very late follow up are needed to better define this finding, its mechanism, how to avoid it, and how to treat it properly.